2019
DOI: 10.1093/ibd/izz144
|View full text |Cite
|
Sign up to set email alerts
|

A Population Pharmacokinetic and Exposure–Response Model of Golimumab for Targeting Endoscopic Remission in Patients With Ulcerative Colitis

Abstract: Background Unlike other anti–tumor necrosis factor alpha antibodies, golimumab does not deliver on its promise of effectiveness for treating patients with ulcerative colitis. We investigated the value of therapeutic drug monitoring for optimizing golimumab therapy. Methods We analyzed the golimumab pharmacokinetics data of 56 patients with moderate to severe ulcerative colitis. Induction and maintenance golimumab concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…The PANTS study, where anti-TNF naïve patients with luminal CD were enrolled at the time of anti-TNF initiation and prospectively observed until treatment discontinuation, reported that low TLs of infliximab (<7 mg/L) or adalimumab (<12 mg/L) at week 14 correlated with primary non-response at week 14 (odds ratio [OR] 0.35, 95% confidence interval [CI] 0.20–0.62, p = 0.00038 for infliximab; OR 0.13, 95% CI 0.06–0.28, p < 0.0001 for adalimumab) and non-remission at week 54 (OR 0.29, 95% CI 0.16–0.52, p < 0.0001 for infliximab; OR 0.03, 95% CI 0.10–0.12, p < 0.0001 for adalimumab) [ 87 ]. Similar associations between TLs and therapeutic outcomes have also been observed for golimumab, both in the post-hoc analysis of the registration trial [ 88 ] and in some observational studies [ 89 , 90 , 91 , 92 ]. Some studies have suggested that specific disease phenotypes might need higher TLs to be adequately controlled.…”
Section: Therapeutic Drug Monitoringsupporting
confidence: 69%
“…The PANTS study, where anti-TNF naïve patients with luminal CD were enrolled at the time of anti-TNF initiation and prospectively observed until treatment discontinuation, reported that low TLs of infliximab (<7 mg/L) or adalimumab (<12 mg/L) at week 14 correlated with primary non-response at week 14 (odds ratio [OR] 0.35, 95% confidence interval [CI] 0.20–0.62, p = 0.00038 for infliximab; OR 0.13, 95% CI 0.06–0.28, p < 0.0001 for adalimumab) and non-remission at week 54 (OR 0.29, 95% CI 0.16–0.52, p < 0.0001 for infliximab; OR 0.03, 95% CI 0.10–0.12, p < 0.0001 for adalimumab) [ 87 ]. Similar associations between TLs and therapeutic outcomes have also been observed for golimumab, both in the post-hoc analysis of the registration trial [ 88 ] and in some observational studies [ 89 , 90 , 91 , 92 ]. Some studies have suggested that specific disease phenotypes might need higher TLs to be adequately controlled.…”
Section: Therapeutic Drug Monitoringsupporting
confidence: 69%
“…For example, all patients in the analysis data set were biological‐naïve, received standard infliximab induction therapy (dose escalations were only performed from week 14 onwards), and had concomitant azathioprine therapy. Previous biological therapy and immunosuppressive comedication have been shown to affect exposure and response to biological therapies 24,44–46 . Therefore, the suitability of our models to inform precision dosing in these patients should be evaluated 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Several realworld studies reported the relationship between golimumab exposure during induction therapy and mucosal healing. [25][26][27] Conversely, the association of SGC with mucosal healing during maintenance has only been evaluated in the real world in a retrospective study that included 19 patients with UC or IBD-unclassified. 28 Although there was a trend towards a higher trough golimumab level in patients with endoscopic remission (defined as an MES of 0 or 1), this difference was not statistically significant, which is most likely due to the small sample size.…”
Section: Discussionmentioning
confidence: 99%